Truth and Its Benefit for Personal Development - Jovaiša, Leonas (Acta Paedagogica Vilnensia, 1996)
The article discusses various aspects of truth. Truth could be viewed as a truth of nature, as an individual truth of a person, as a truth of special and universal sciences, as a truth of a society. The aim of the article is to show that school can accomplish its mission if it relies on eternal truths of nature and spiritual life. Education should stay above the routines of the everyday life and raise to the heights of science, religion, art and technology. It is the point of departure from which the perspectives of tomorrow might be seen.
Keywords: Education; spiritual life; truth of nature; individual truth; truth of a society.